Cyprus Language Centres: profiles and survival strategies in an era of diminishing resources - Papadima-Sophocleous, Salomi; Parmaxi, Antigoni (My University, 2016)
In the history of universities, one can notice the coexistence of schools, faculties, departments, Language Centres (LCs) and language resource centres. The establishment of the last two came out of further need to support students and other university and broad community members to explore and expand their language horizons. Changes in learning and teaching provision, methods and approaches, and the use of new technologies contributed in the development of the operation of such centres. Their nature depends on the varied needs of each institution and its community. They may offer compulsory or elective language courses, language independent study programmes, extended learning through a variety of approaches and techniques, and printed and digital materials. All of that is carried out through new ways of learning such as blended, online, independent or autonomous learning. The aim of this paper is three fold: (a) to review a substantial number of existing Language Centres (LCs) in different parts of the world in order to form a set of general parameters of what currently constitutes a university LC; (b) to use these parameters to review the university LCs that have been established in the last 25 years in seven newly established universities in the Republic of Cyprus in order to also establish their type and how they fit in this framework; and finally since worldwide there are economic constraints in all spheres of life, (c) to record the survival strategies that LCs employ in Cyprus, in an era of diminishing resources. A review of the websites of LCs around the world was carried out, followed by a review of the different types of LCs in the seven universities in the Republic of Cyprus. Interviews with the directors of the LCs were also conducted in order to collect further data. LCs in Cyprus generally reflected the 12 parameters commonly formed through the study of the LCs in different parts of the world. Finally, the survival strategies of the LCs in Cyprus were explored and suggestions for course of action were put forward.
INTED2016 Proceedings
Keywords: Language centers; Survival strategies; Economic constraints